Mailed Art in Uppsala : Choosing your partner - Meyer, Peter R. ([S.l.] : Peter Meyer, 1994)
Johnson, Ray ; Baroni, Vittore ; Bleus, Guy ; Vigo, Edgardo ; Pittore, Carlo ; Crozier, Robin ; Cavellini, Guglielmo ; Banana, Anna ; Spiegelman, Lon ; Groh, Klaus ; etc.
Mailed Art in Uppsala Choosing your partner, 4 june - 17 september 1994
Engels & Zweeds
boek